Taxation in Electronic Commerce (Journal of the College of Basic Education, 2022)
E-commerce is a form of commercial cooperation, which includes electronic interaction between the parties participating in the process of trade exchange, instead of tangible interaction, or direct connection [1] (Al Allak, 2003,p 149), E-commerce implies the implementation of electronic transactions on the exchange of documents, e-mail, electronic newsletters, fax, e-money and other electronic means [2] (Radhwan, 1999,p 15